High-Flow Nasal Cannula vs. Continuous Positive Airway Pressure Therapy for the Treatment of Children <2 Years With Mild to Moderate Respiratory Failure Due to Pneumonia - Liu, Cong; Cheng, Wei Yu; Li, Jun Shao; Tang, Tian; Tan, Ping Li; Yang, Lin (Frontiers in Pediatrics, 2020)
Background: The aim of this prospective randomized controlled study was to further compare the clinical benefits and adverse reactions of HFNC with CPAP in the treatment of mild to moderate respiratory failure due to pneumonia in children below 2 years old. Methods: Using a prospective randomized controlled study method, 84 patients with pneumonia and mild to moderate respiratory failure admitted to the Children's Hospital Affiliated to Chongqing Medical University from January 2018 to December 2019 were randomly divided into the HFNC group and the CPAP group .It was registered as a clinical trial at clinical trials.gov, registration number: ChiCTR2000030463. Results：The analyses included 84 patients. No differences were observed between the two groups in baseline demographic or physiological characteristics. Treatment failure necessitating intubation and transfer to the PICU was noted in 6 of 43 infants (14%) in the HFNC group, as compared with 4 of 41 infants (10%) in the CPAP group (P＞0.05). There were no significant differences between the two groups in the duration of hospital stay, the duration of noninvasive respiratory support, and mortality. The 10 infants who experienced treatment failure had more severe hypoxemia with lower PaO2/FiO2 (HFNC 182 ± 11.5，and CPAP 172 ± 8.6). We found that both the HFNC group and the CPAP group showed significantly improved oxygenation and relief of respiratory distress after treatment. No differences were observed between the two groups in the development improvement of RR, PaO2, PaCO2, SpO2, and PH. Assessment of the occurrence of adverse events showed that the HFNC group had a lower level of nasal injury, a lower risk of abdominal distension, a lower intensity and frequency of sedation, and better tolerance. Conclusion: HFNC is an effective and safe initial respiratory support treatment in children <2 years with mild to moderate respiratory failure due to pneumonia, and the incidence of intubation and death is very low; concurrently, the comfort and tolerance of HFNC are better. To some extent, HFNC is a well-tolerated alternative to CPAP.